The Effect Of Placement And Workload On Employee Performance With Motivation As A Mediation Variable at PT. Bank Lampung - Anita Octavia GULTOM; RR ERLINA; Nova MARDIANA (International Journal of Environmental, Sustainability, and Social Science, 2022)
The role of HR in the company is very important in the company's activities. Factors such as work placement, workload, and work motivation are important factors that determine employee performance. This study aims to determine the effect of work placement and workload on employee performance which is mediated by work motivation in employees of PT Bank Lampung. The sample of this research is 252 employees of PT. Lampung Bank. Data collection through a questionnaire based on a stratified random sampling technique and processed using Structural Equation Modeling (SEM) with the help of AMOS software. The results of this study indicate that employee placement has a positive and significant effect on employee performance, the workload has a positive and significant effect on employee performance, employee placement has a positive and significant effect on work motivation, the workload has a negative and insignificant effect on work motivation, work motivation has a positive effect and significant to employee performance, employee placement has an indirect effect on employee performance through the mediating variable of work motivation, and workload has an indirect effect on employee performance through the mediation variable of work motivation. This needs to be considered by the management of PT. To increase motivation and performance, Bank Lampung pays attention to the placement and workload of each employee according to the field and expectations so that the company's goals can be achieved.